ความงามของธรรมชาติที่ส่งผลต่อการสร้างสรรค์จิตรกรรมของศิลปิน - นรินทร์ ฟองฟูม (คณะศิลปกรรมศาสตร์ จุฬาลงกรณ์มหาวิทยาลัย, 2022)
The Beauty of Nature that Affect the Creative Paintings of the Artist was the creative research. The purpose of this research was to study how to create paintings that create convey positive emotions from the beauty of nature. Currently, the natural resources and the environment are deteriorating due to destruction cause by logging and burning forest which can occur for many reasons, such as using trees for charcoal to use or sell as foodstuffs. Using natural resources without substituting sufficient amounts to all causes humans to neglect the importance of nature. Therefore, the research results present the beauty of nature to realize the value of nature. The research process begins with studying the beauty of nature. The beauty of nature that has influenced the researcher s creativity studied the perception theories, emotion theories, color theory, and Psychology of color. To find ways to use colors that affect their true feelings towards the study of artists in various creeds related to the creation of paintings. To study various techniques in conveying the impression of the atmosphere through colors natural light, shadow, etc. The research results were accomplish the purpose. The audiences are interested and aware of the importance of nature. The paintings can create a positive feeling about nature. In addition, the creation of the work demonstrates the atmosphere and colors in the shade of nature by the impressionist art style. There is the development of unique works of painting by using mostly cool colors and rhythmic strokes to brush the brush to convey the emotions of the researchers to the public.